2021
DOI: 10.1002/pssa.202100494
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer and Quenching in Sol–Gel‐Derived Silica Glass Green Phosphors Doped with Tb3+ and Ce3+ Ions: Distinct Difference between P‐ and Al‐Codoped Glasses

Abstract: The (Tb,Ce)−P‐codoped silica glasses containing (Tb,Ce)PO4 nanocrystals (silica−(Tb,Ce)PO4 glass‐ceramics) and (Tb,Ce)−Al‐codoped silica glasses are prepared by a cosolvent‐free sol−gel method. They emit bright green photoluminescence (PL) attributed to the 5D4 → 7F j (j = 1 − 6) transition of Tb3+ ions under excitation at 290 nm into the 4f−5d transition of Ce3+ ions. The (Tb,Ce)−P‐codoped silica glass prepared at the P to rare‐earth (RE) molar ratio of 2 exhibits the internal and external PL quantum efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Several publications have been devoted to doping RE ions into sol–gel-derived silica glass, which is commonly co-doped with P or Al. These two elements facilitate the dissolution of RE ions in silica glasses due to the selective coordination strength of PO 4 or AlO x units [ 23 , 24 , 25 , 33 , 34 , 35 , 36 ]. Another way to incorporate SrAl 2 O 4 into SiO 2 glass is to use ready-made SrAl 2 O 4 phosphor powder obtained by solid-state or sol–gel synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several publications have been devoted to doping RE ions into sol–gel-derived silica glass, which is commonly co-doped with P or Al. These two elements facilitate the dissolution of RE ions in silica glasses due to the selective coordination strength of PO 4 or AlO x units [ 23 , 24 , 25 , 33 , 34 , 35 , 36 ]. Another way to incorporate SrAl 2 O 4 into SiO 2 glass is to use ready-made SrAl 2 O 4 phosphor powder obtained by solid-state or sol–gel synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Additional steps were added to this synthesis process to obtain 2 wt% SrAl 2 O 4 :Eu, Dy, and B in SiO 2 glass. According to Kajihara et al [ 23 , 24 , 25 ], the formation of SrAl 2 O 4 :Eu, Dy, and B particles in the sol–gel-derived SiO 2 glass matrix was expected to occur. Samples with different concentrations of boron (0 at% for comparison and three concentrations—7, 10, and 15 at% B—as the optimal concentrations for powder material by Vitola et al [ 26 ] were synthesized and investigated, as it was previously shown to greatly affect the luminescent properties of the resulting sample [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…In such cases, PL may be significantly weakened by quenching centres even if their concentration is low. Indeed, the IQE of green PL from Tb 3+ ions in a silica-(Tb,Ce)PO 4 glass was dropped from ∼0.99 to ∼0.02 by an addition of 1 at% of quenching centres (Nd 3+ ions) [21,22]. The IQE of PL from the 6 P 7/2 state of Gd 3+ ions in the silica-(Gd,Pr)PO 4 glass used in this study is close to 1 (∼0.98) at room temperature, indicating that quenching centres are almost absent in (Gd,Pr)PO 4 nanocrystals in this glass-ceramic.…”
Section: Resultsmentioning
confidence: 99%